REGRESSION MODELS OF THALAMUS DIMENSIONS IN BOYS AND GIRLS OF DIFFERENT CRANIOTYPES - I. V. Gunas; L.V. Babych; O.I. Kovalchuk; E.V. Cherkasov; F.V. Shayuk (Bogomolets National Medical University, 2017)
In 82 practically healthy urban youths and 86 girls of the Podillia region of Ukraine, when distributed into different craniotypes, reliable regression models of computational-tomographic dimensions of thalamus were constructed depending on anthropometric and somatotypological parameters with a determination coefficient greater than 0.6. In mesocephalic boys, of 4 possible models, 3 were constructed with a determination coefficient from 0.731 to 0.938; and in brachycephals boys only 1 model (the determination coefficient is 0.620). In girls-dolichocephals and brachycephals all 4 models have been constructed (accordingly, the determination coefficient is from 0.750 to 0.926 and from 0.760 to 0.925); and in mesocephalic girls only 2 models (the determination coefficient is 0.640 and 0.690). The built models most often included: in mesocephalic boys - the circumferential dimensions of the body and the thickness of skin and fat folds (by 25.0%); in dolichocephals girls - body diameters (26.9%) and evenly cephalometric indices, total, longitudinal, circumferential sizes of the body and width of distal epiphyses of long limb bones (by 11.5%); in mesocephalic girls, the thickness of skin and fat folds (30.8%) and the width of distal epiphyses of long limb bones (23.1%); in girls brachycephals - the circumferential dimensions of the body (30.8%), body diameters (26.9%), and the thickness of skin and fat folds (19.2%).